2015
DOI: 10.1111/wvn.12122
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lavender Tea on Fatigue, Depression, and Maternal‐Infant Attachment in Sleep‐Disturbed Postnatal Women

Abstract: Healthcare researchers assume accountability for integrating research results into clinical practice. The findings in this study can gain greater attention among healthcare practitioners and encourage the correct and positive use of herbal therapy in postpartum health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 63 publications
0
46
0
6
Order By: Relevance
“…In postpartum mothers lavender inhalation aromatherapy is reported to have a hypnotic effect, act as a mood stabilizer, and enhance the positive feelings about their infants. Taiwanese postnatal women with poor sleep quality were treated with lavender tea and the participants perceived less fatigue and depression and showed greater bonding with their infant compared with the control group, suggesting that the positive effects of lavender tea were limited to the immediate term 17 .…”
Section: Discussionmentioning
confidence: 99%
“…In postpartum mothers lavender inhalation aromatherapy is reported to have a hypnotic effect, act as a mood stabilizer, and enhance the positive feelings about their infants. Taiwanese postnatal women with poor sleep quality were treated with lavender tea and the participants perceived less fatigue and depression and showed greater bonding with their infant compared with the control group, suggesting that the positive effects of lavender tea were limited to the immediate term 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Kişisel bilgi formu, araştırmacılar tarafından literatüre dayalı olarak (2,10,18,29) (6,7,8,9, 10 numaralı maddeler) olmak üzere iki alt boyuttan ve 18 maddeden oluşmaktadır. YİBGS'nın bir ucunda olumlu, diğer ucunda ise olumsuz sözlerin yer aldığı 10 cm uzunluğunda yatay çizgiler bulunmaktadır.…”
Section: Araştırmanın Amacı Ve Araştırma Sorularıunclassified
“…Yapılan çalışmalarda, doğum sonrası yorgunluk görülme sık-lığının %18 ile %96 arasında değiştiği rapor edilmektedir (3)(4)(5)(6) . Doğum sonrası yorgunluk, kadının iyileş-mesini, annelik davranışlarını, bebek bakımı aktivitelerini, aile üyeleri ile ilişkilerini, iş performansını, özbakım gücünü ve yaşam kalitesini olumsuz etkilemektedir (7,8) . Ayrıca yorgunluk, anne-bebek ilişkisi-nin ve bebeğin büyüme-gelişmesinin olumsuz etkilenmesine neden olabilir (9,10) .…”
Section: Introductionunclassified
“…For instance, in randomized controlled studies, Balouchi et al . () and Chen and Chen () found that aromatherapy with lavender significantly decreased fatigue (Chen and Chen, ; Balouchi et al ., ). Tahmasebi et al .…”
Section: Introductionmentioning
confidence: 99%